2019
DOI: 10.3847/1538-4357/ab03d1
|View full text |Cite
|
Sign up to set email alerts
|

A Three-dimensional View of Molecular Hydrogen in SN 1987A

Abstract: Supernova (SN) 1987A is the only young SN in which H 2 has been detected in the ejecta. The properties of the H 2 are important for understanding the explosion and the ejecta chemistry. Here, we present new VLT/SINFONI observations of H 2 in SN 1987A, focussing on the 2.12 µm (1,0)S(1) line. We find that the 3D emissivity is dominated by a single clump in the southern ejecta, with weaker emission being present in the north along the plane of the circumstellar ring. The lowest observed velocities are in the ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…However, this process clearly only operates in the outward direction, which leads us to conclude that elements that originate further out in the progenitor, including H, must have been mixed down to velocities of only a few 100 km s −1 in the explosion itself. Similarly low velocities for H have been observed also in SN 1987A (Kozma & Fransson 1998;Larsson et al 2019) and reproduced in simulations of neutrino-driven explosions (Utrobin et al 2019).…”
Section: The Innermost Regionsupporting
confidence: 73%
“…However, this process clearly only operates in the outward direction, which leads us to conclude that elements that originate further out in the progenitor, including H, must have been mixed down to velocities of only a few 100 km s −1 in the explosion itself. Similarly low velocities for H have been observed also in SN 1987A (Kozma & Fransson 1998;Larsson et al 2019) and reproduced in simulations of neutrino-driven explosions (Utrobin et al 2019).…”
Section: The Innermost Regionsupporting
confidence: 73%
“…The precise origin of the Hα hole, whether from a physical lack of material (due to the reverse shock or a simple void due to the expansion of ejecta), or illumination of the ring X-rays brightening the outer rim of the ejecta, or from dust extinction, has been discussed for many years (e.g., McCray 2003; Larsson et al 2011;Fransson et al 2013;Larsson et al 2016Larsson et al , 2019. A simple estimate of the extinction can be made by assuming the dust fills a spherical shell with uniform density, and calculating the optical depth using the mass extinction coefficient κ ext (related to, but different from the κ abs used in the modBB fits) according to τ λ = κ ext,λ ρ ds.…”
Section: Dust As a Source Of Extinctionmentioning
confidence: 99%
“…Fransson et al ( 2016) reported the discovery of infrared H2 molecular lines. The power source suggested for these lines was 44 Ti decay, as the lines were more centrally concentrated than the edge-brightened Hα emission (and indeed X-rays from the ejecta-ER interaction could dissociate the molecules) -this is also supported by a lack of time evolution in the infrared H2 flux (Larsson et al 2019a). The possible excitation mechanisms not related to X-rays from interaction are non-thermal electrons, from cascades caused by positrons from the 44 Ti decay; and UV continuum fluorescence by photons generated internally within the ejecta.…”
Section: Excitation Of the Molecular Hydrogenmentioning
confidence: 94%
“…Orlando et al 2015;Wongwathanarat et al 2015), has been studied previously by e.g. Kjaer et al (2010) and Larsson et al (2013Larsson et al ( , 2016Larsson et al ( , 2019a. The structure was shown to be asymmetric, its emission predominantly blueshifted in the northern part and redshifted in the south (Kjaer et al 2010) in a 'broken dipole' (Larsson et al 2016).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation